Religious and Community Leaders' Perspectives on Minor Marriage Resulting From Unwed Pregnancy - Alfarisi, Usman; Riswandi, Fajar; Dzakira, Abidah; Selvita, Amanda; Zulfikar, Ahmad Farhan; Rosfiani, Okta (Journal of Modern Islamic Studies and Civilization, 2024)
Instances of unwed pregnancy leading to teenage marriage are common throughout different areas. Recently, adultery has become more common in Indonesian society, particularly in the community of Kota Bambu Utara subdistrict. Teenagers in North Bambu City Village nowadays are therefore frequently involved in the problem of promiscuity, which leads to adultery, and as a result, many of them become unwed mothers who later get married while still pregnant. The purpose of this study is to find out what the religious and community leaders in Kota Bambu Utara Village, Palmerah District, think about underage marriage as a result of unwed pregnancies. This kind of research is qualitative in character and falls under the case study category. The key sources of data for this study were informants who provided primary sources. The primary sources of information for this study were religious and community leaders in Kota Bambu Utara Subdistrict. Researchers used documentation, interviews, and observation to gather data for their study. The study's findings indicate that, despite the marriage law's regulation of the legal age restriction for those seeking marriage, underage weddings resulting from unwed pregnancies typically happen between the ages of 15 and 17. A minor who does not meet the conditions for marriage must request a dispensation from the West Jakarta Religious Court in order for their marriage to proceed. A number of circumstances, such as the individual's behavior, influences from parents and family, a lack of education and religious understanding, and social elements in the area, can lead to underage marriage owing to unwed pregnancy.